Implementation of Project-Based Learning Assisted by Simlitar Media to Improve Creative Thinking Abilities and Student Learning Outcomes - Pramesti, Tita Ayu; Hadiyanti, Agnes Herlina Dwi; Ernawati, Ernawati (Teknodika, 2023)
The project-based learning model is deemed to be a student-centered model when applied to learning activities. It undoubtedly opens higher opportunities for students to optimize their abilities, and hopefully, they can achieve the competencies set in the learning objectives. This research, therefore, aims to improve the creative thinking abilities and learning outcomes of third-grade elementary school students in Yogyakarta, assisted by Simlitar Media, through a project-based learning model. The type of research used was classroom action research (PTK). The research subjects were 26 students. Data collection was carried out through interviews, observations, and tests. The data analysis techniques employed were qualitative and quantitative. Based on the results of this research, the project-based learning model could improve students' creative thinking abilities and learning outcomes. From the results of data analysis and discussion in this research, there was an increase in students' creative thinking abilities from the pre-cycle stage to cycle 2, which initially averaged 27% to 88%. The average creative thinking ability of students in one class increased by 61%. Student learning outcomes also increased from the pre-cycle stage to cycle 2. The average completeness of student learning outcomes in the pre-cycle stage was 15%, becoming 88% in cycle 2. The average completeness of third-grade students' overall learning outcomes increased by 73%. Hence, it can be concluded that the application of this learning model accompanied by Simlitar media has been proven to improve creative thinking abilities and student learning outcomes